Increased Occurrence of Valproic Acid-Induced Hyperammonemia in Carriers of T1405N Polymorphism in Carbamoyl Phosphate Synthetase 1 Gene. (7th August 2013) - Janicki, Piotr K.; Bezinover, Dmitri; Postula, Marek; Thompson, Robert S.; Acharya, Jayant; Acharya, Vinita; McNew, Cathy; Bowman, J. Daniel; Kurkowska-Jastrzebska, Iwona; Mirowska-Guzel, Dagmara
Abstract : Numerous cases of severe and life-threatening hyperammonemia (HA) related to the treatment of epileptic seizures with valproic acid (VPA) have been previously reported in the medical literature. The aim of this prospective, multicenter study was to verify the putative association between T1405 polymorphism and occurrence of VPA-induced HA in the cohort of 142 adult Caucasian patients with epilepsy treated with VPA for at least 1 year and with normal liver functions. The nonsynonymous T1405N polymorphism genotyping was performed by real-time TaqMan PCR genotyping. In addition to plasma ammonia level, concentrations of liver enzymes and total VPA were measured in plasma with standard laboratory methods. HA (defined as ammonia plasma level >65  μ mol/L) was observed in total of 11 (7.7%) of patients treated with VPA, and the carrier status for the investigated polymorphism was significantly (P = 0.009, odds ratio 5.4 with 95% confidence interval of 1.58–18.43) associated with the occurrence of HA. The results of this study support a notion that in the Caucasian patients with epilepsy undergoing VPA therapy, a T1405N (4217C > A, rs1047891) nonsynonymous variant was a significant risk factor for the occurrence of HA, even in patients with normal plasma levels of VPA.